2017
DOI: 10.1177/0706743717730825
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship between Disordered Gamblers with Psychosis and Increased Gambling Severity: The Mediating Role of Impulsivity

Abstract: Impulsivity appears to be a transdiagnostic process that may be targeted in treatment among disordered gamblers with a dual diagnosis of psychosis to reduce problematic gambling behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Indeed, the results have additional clinical implications. Recently, researchers have begun investigating transdiagnostic mechanisms (e.g., impulsivity and emotion dysregulation) that may account for the relationship between disordered gambling and increased severity among gamblers with a psychiatric comorbidity (Kim et al, in press). A benefit of identifying transdiagnostic processes is that they can be targeted in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the results have additional clinical implications. Recently, researchers have begun investigating transdiagnostic mechanisms (e.g., impulsivity and emotion dysregulation) that may account for the relationship between disordered gambling and increased severity among gamblers with a psychiatric comorbidity (Kim et al, in press). A benefit of identifying transdiagnostic processes is that they can be targeted in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we have assessed whether similar component vulnerabilities represent common factors that exacerbate the severity of mental health and addictive disorders. For example, we have found that heightened levels of impulsivity mediate the relationship between dual diagnosis of gambling and psychosis, and increased gambling severity ( 180 ). Relatedly, we have found that maladaptive expectancies mediate the relationship between co-morbid gambling and depression, and increased gambling severity.…”
Section: Current and Future Directionsmentioning
confidence: 99%
“…In Sweden, antipsychotic drugs were dispensed to about 2% of the general population, a number appearing to be quite stable during the study period (Swedish National Board of Welfare, 2020b). Prevalence rates of psychotic disorders are reported to be about 4% in the general population, with a corresponding number of 7% in problem gamblers (Kim et al, 2018;Moreno-Kustner et al, 2018); hence, it is likely that many of the patients studied here were prescribed antipsychotic drugs on other indications than actual psychotic disorders. Increases of off-label prescription of atypical antipsychotic drugs for several psychiatric disorders have been reported, despite highly limited evidence (Albert et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Increases of off-label prescription of atypical antipsychotic drugs for several psychiatric disorders have been reported, despite highly limited evidence (Albert et al, 2016). More attention needs to be drawn to the association between psychoses and GD, since this type of comorbidity may contribute to a higher gambling severity due to greater levels of impulsivity, and reward-directed behavioral disturbance requiring targeted treatment (Kim et al, 2018). Some dopamine antagonists themselves have been reported to, paradoxically as it may seem, increase the rewarding and priming effect of gambling in individuals with GD (Zack & Poulos, 2007).…”
Section: Discussionmentioning
confidence: 99%